Statistical characteristics of locally generated ESF during equinoctial months over Sanya. Issue 9 (1st May 2018) - Meng, Xing; Fang, Hanxian; Li, Guozhu; Weng, Libin
Abstract: Understanding the local generation rate of equatorial spread-F (ESF) is important for forecasting ionospheric scintillation. Using the GPS ionospheric scintillation/TEC and VHF radar data during March-April and September-October from 2010 to 2014, the occurrence of ionospheric scintillation, TEC fast fluctuation, and backscatter plume were studied. Through analyzing the simultaneous occurrence of ionospheric scintillation, TEC fast fluctuation and backscatter plume, the local generation rate of ESF over Sanya was investigated. The results show that the monthly generation rate varies between 0% and 68%. A significant equinoctial asymmetry of local generation rate of ESF can be found in 2010, 2013 and 2014. The local generation rate of ESF increases from 2010 to 2014 during March-April, while it does not have similar trend during September-October. The plasma vertical drift influenced by solar activity has a significant impact on the monthly generation rate. The equinoctial asymmetry of plasma vertical drift may contribute a lot to the equinoctial asymmetry of the generation rate of ESF.